The Extended Classroom Framework for Teaching Systems Analysis of Food Systems. Issue 1 (18th December 2015) - Runck, Bryan C.; Brakke, Mary P.; Porter, Paul M.
Abstract : To further synthesize Systems Action Education (SAE) and adventure learning (AL), a new education framework is presented called the Extended Classroom Framework (ECF) for teaching systems analysis of food systems. Extended Classroom Framework integrates SAE and AL with the circulatory system of science to describe how the classroom interacts with society. In the fall of 2012, the ECF was utilized to design a hybrid course at the undergraduate level that explored four different international agroecoregions through the perspective of on‐the‐ground collaborators. By utilizing online geographic information systems and an online social network, students digitally explored these agroecosystems as open‐ended cases. A pre‐ and post‐test of the Intercultural Development Inventory was given to the students. Students also wrote four reflective journals that were coded and thematically analyzed. Six of seven of students showed positive shifts in their developmental orientation ( p < 0.05). Four of seven students showed decreases in their intercultural orientation gap. Every student ended the course similarly or less culturally disengaged to a primary cultural group, with six students in the resolved category compared with four at the beginning of the course. Student reflective journals illustrated growth in considering agroecosystems contextually and as coupled human–environmental systems. These results show that the ECF offers a viable framework for developing student capacities to engage "wicked" problems. Impact Statement The Extended Classroom Framework (ECF) provides a means to synthesize online GIS and social networks to allow students and instructors to experientially learn about human–environment interactions in multiple international contexts in a cost‐effective manner. By providing preliminary evidence documenting the framework in action, this article shows the ECFs potential to increase students' ability to think systemically and work across differences, essential skill sets for practitioners working within "wicked problems."